The Relationship between Emotion Regulation and Adult Attachment: A Correlational Study - Sultana, Robina; KanwalYamin, Huda; Hanif, Asma; Jawad, Momina; Zubairi, NabeelAhmed (Current Progress in Arts and Social Studies Research Vol. 10, 2025)
Emotional regulation refers to the ability to manage and control emotions effectively. Adult attachment styles, which are shaped by early childhood experiences, play a significant role in how individuals relate to others and experience emotions. Secure attachment supports healthy emotional regulation, enabling individuals to understand, express, and manage their feelings appropriately. In contrast, insecure attachment styles, such as anxious-preoccupied, dismissive-avoidant, or fearful-avoidant, can impair emotional regulation, leading to challenges in managing stress, anxiety, and other emotions. The aim of our study was to explore the correlation between adult attachment styles and emotional regulation. It was hypothesized that (1) there would be a positive correlation between secure attachment style and high emotional regulation, and (2) anxious and dependent attachment styles would be positively correlated with poor emotional regulation. The sample was collected using a convenient sampling method and data of 136 participants aged 18 to 30 years was used. Two self-report scales were; The Adult Attachment Scale (close version) was used to assess attachment styles, while the Emotional Regulation Questionnaire (ERQ) measured participants’ ability to regulate emotions. Participants filled out the questionnaire individually. After scoring the raw data, Pearson’s correlation analysis was conducted to examine relationships between the variables. The results of the study revealed correlation values as follows: reappraisal with closeness (r=-0.133), reappraisal with dependence (r=-0.125), suppression with closeness (r=-0.282), suppression with dependence (r=-0.334), reappraisal with anxiety (r=-0.125), and suppression with anxiety (r=0.214). Contrary to our first hypothesis, there was no significant correlation between secure attachment styles and emotional regulation. The second hypothesis was partially supported, showing a weak positive correlation between suppression and anxiety, as well as a negative weak correlation between suppression and dependence. Overall, our findings challenge the assumed relationship between attachment styles and emotional regulation, revealing unexpected weak correlations.